THE ROLE OF EXTRAVAGANCE IN ISLAMIC LAW: A HISTORICAL STUDY - Assist. Lect. Baydaa Talib Abdulhasan (American Journals Publishing, 2024)
It wouldn't be far from the truth to say that money ranks among the most essential needs for individuals in this worldly life. It serves as a means to secure life's necessities, including food, drink, clothing, shelter, and other essentials that form the foundation of one's material existence. The availability of money varies among people, with some falling into the category of "the rich" while others are labeled as "the poor." The abundance of money is often associated with worldly success, a weakening of faith, and the acquisition of advantages that set individuals apart, such as status, position, beauty, or other benefits that contribute to the emergence of luxury and its underlying causes.This study aims to illuminate a phenomenon that has persisted in many affluent societies. We have elucidated the stance of the Holy Qur’an on extravagance, as evidenced by approximately twenty-three verses that condemn and caution against it. Additionally, we have highlighted select noble prophetic traditions that illustrate the Prophet's stance on extravagance and its impact on individuals and society. In addition to Prophet Muhammad's stance, which rejects such conduct and its detrimental impacts from a religious, material, social, psychological, and economic standpoint, we have also covered the Ahl al-Bayt's (peace be upon them) stance. Jurisprudential and historical materials provide the basis of this study.
Keywords: Extravagance, Sunnah of the Prophet, Antiquities, the Holy Qur’an Position